Pendampingan Penerapan Metode Field Trip bagi Guru SD SMP dan SMA di Kabupaten Timor Tengah Utara - Taneo, Malkisedek; Madu, Aleksius; Krisnawati, Nova (LP2M INSURI Ponorogo, 2023)
The lack of teacher creativity to design teaching and learning activities by applying various teaching methods suitable for the characteristics of the students' subject matter, situation, or condition is one of the problems in learning. This community service aims to support educators in Noemuti District, North Central Timor Regency, in carrying out activities to compile learning tools based on field trip learning methods, carry out learning in the classroom, and write scientific articles. The plans for this activity are training and mentoring strategies. Exercise is related to planning, action, observation and evaluation, and reflection, while mentoring is carried out outside this training activity according to the needs of learners in the field. Participants in this training came from teachers in the Noemuti sub-district, including elementary, junior high, and high school teachers. The material provided in this activity is related to the field trip learning method, the preparation of learning tools based on the steps of the field trip learning method, simulation of teaching and learning activities both in the room and out of the classroom. The results achieved in this service activity where teachers with different educational backgrounds can be guided in preparing learning tools based on field trip learning methods, and implementing them in class, making scientific articles to be published. In addition, although quantitatively, this activity still does not provide maximum results, qualitatively, these teachers are helped by the learning practices carried out by the service team. They can then be used as an alternative teaching model that can be implemented in their schools.